The roles of cannabis potency and gender in cannabis dependence and anxiety in recent cannabis users with trauma exposure histories - T. Snooks; S.H. Stewart; P. Romero-Sanchiz; S. DeGrace; S.P. Barrett; H.C.R. Bernusky; P.G. Tibbo (Pharmacological Research)
Over the past 20 years, levels of Δ9-tetrahydrocannabinol (THC) in cannabis have significantly increased, while levels of cannabidiol (CBD) have increased much less in comparison. Cannabis with higher THC potency (commonly assessed via THC:CBD ratio) may increase the risk for cannabis dependence and trigger/exacerbate anxiety. However, few studies of cannabis potency effects on cannabis dependence and anxiety have examined gender moderation. Additionally, there are issues with how cannabis potency is calculated via the THC:CBD ratio that may contribute to inconsistencies in the literature. N = 202 (55.8 % women) recent cannabis users (>1 g in the past month) with trauma histories – a group at high risk for anxiety and cannabis dependence – completed an online survey including a self-report measure of THC and CBD levels in participants’ typically-used cannabis product. Cannabis potency was calculated as THC:CBD ratio (THC%/CBD%) and as relative THC proportion (THC%/[THC%+CBD%]). Cannabis dependence and anxiety levels were self-reported on the Cannabis Use Disorder Identification Test-Revised (CUDIT-R) and Generalized Anxiety Disorder-7 (GAD-7), respectively. Consistent with prior findings in the general population, cannabis potency was significantly positively correlated with cannabis dependence, p = .002, and anxiety levels, p = .020, but only when assessed via THC proportion and not THC:CBD ratio. Consistent with prior research, women reported significantly higher anxiety levels but also unexpectedly, higher THC:CBD ratios, than men. No significant gender differences were found in the associations of either potency measure with either outcome variable. Results are consistent with recent reports of gender convergence in cannabis use prevalence. Additionally, these results identify relative THC proportion as a superior predictor of adverse cannabis and anxiety outcomes than the THC:CBD ratio in both men and women.